PENINGKATAN HASIL BELAJAR MELALUI IMPLEMENTASI MEDIA BELAJAR MIKA HOLOGRAM 3D PADA PEMBELAJARAN IPA SD KELAS 5 : Peningkatan Hasil Belajar IPA SD Kelas 5 - Aditya Dwi Pratama; Muhamad Sofian Hadi (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This research aims to explore the improvement of concept understanding through the implementation of the 3D Hologram Mica learning media in the teaching of Natural Sciences for 5th-grade elementary school students. The research method used was classroom action research involving one experimental class using the 3D Hologram Mica learning media and one control class using conventional teaching methods. The population of this research consisted of 5th-grade students in an elementary school in an urban area. The research sample consisted of 18 randomly selected students divided into two groups. Data were collected through concept understanding tests before and after the implementation of the 3D Hologram Mica learning media, as well as classroom observations and interviews with the teacher. The results of the research show that the implementation of the 3D Hologram Mica learning media significantly improves students' learning outcomes. There is a significant increase in the average scores of students' learning outcomes after the implementation of the 3D Hologram Mica learning media compared to the previous scores. The average score obtained in the pre-cycle activities was 69.3 with a class mastery level of 38%. Then, an action was taken by implementing the Mica Hologram 3D learning media in the second cycle phase, and an average score of 76 was obtained with a class mastery level of 55%. As it did not reach the minimum mastery level of 80%, the research proceeded to the second cycle action, and the average score obtained was 86 with a class mastery level of 88%. With these results, the action was stopped in the second cycle, showing a learning mastery improvement of 17% from pre-cycle to cycle I, and 33% from cycle I to cycle II. In addition, classroom observations and interviews with the teacher revealed positive responses from students toward the use of this learning media, which involved engaging three-dimensional visualization. Based on these findings, it can be concluded that the implementation of the 3D Hologram Mica learning media in teaching Natural Sciences to 5th-grade elementary school students is effective in improving concept understanding. It is recommended for teachers and other schools to consider the use of this innovative learning media as a teaching aid that can enhance learning outcomes and the quality of Natural Sciences education at the elementary school level.